2011
DOI: 10.2478/v10078-011-0082-1
|View full text |Cite
|
Sign up to set email alerts
|

Position-Related Differences in Cardiorespiratory Functional Capacity of Elite Basketball Players

Abstract: The purpose of this study was to examine possible differences in cardio respiratory functional capacity between perimeter and post elite basketball players. The subjects included 42 highly trained basketball players subdivided into groups of perimeter and post players. Point guards, shooting guards and small forwards were involved in the group of perimeter players, while power forwards and centers represented the group of post players. All players performed a standardized exercise test to evaluate maximal oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
3
11
1
2
Order By: Relevance
“…This was in agreement with previous research in France [3] and in Bosnia [4], whereas other research revealed differences only between centers and guards in Belgium [5] or that centers and forwards did not differ [2]. Post-players have also been found taller than perimeter players [7]. All studies have shown the same trend even when the differences were not significant; centers were taller than forwards and guards, and forwards were also taller than guards.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This was in agreement with previous research in France [3] and in Bosnia [4], whereas other research revealed differences only between centers and guards in Belgium [5] or that centers and forwards did not differ [2]. Post-players have also been found taller than perimeter players [7]. All studies have shown the same trend even when the differences were not significant; centers were taller than forwards and guards, and forwards were also taller than guards.…”
Section: Discussionsupporting
confidence: 91%
“…We did not find any positional difference, whereas it had been suggested that guards had better aerobic power than forwards [5] and centers [2,3,5]. On the other hand, perimeter players from the Lithuanian league (FIBA world ranking 4th) had similar VO 2max with postplayers when oxygen uptake was in ml min -1 [7]. Therefore, it seems that in the top level positional differences for aerobic power are decreased or eliminated.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations